2018
DOI: 10.1093/ofid/ofy044
|View full text |Cite
|
Sign up to set email alerts
|

Severe Community-Acquired Pneumonia due to Acinetobacter baumannii in North America: Case Report and Review of the Literature

Abstract: Acinetobacter baumannii is a rare but emerging cause of fulminant community-acquired pneumonia (CAP-AB). We describe a patient from a rural area who developed acute respiratory distress syndrome and septic shock. We describe risk factors and characteristics of this syndrome and review published cases of CAP-AB from North America.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
25
0

Year Published

2018
2018
2021
2021

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 35 publications
(36 citation statements)
references
References 22 publications
2
25
0
Order By: Relevance
“…CAP cases caused by A. baumannii are very rare in Europe and USA. A recent USA case report of severe CAP and review of the literature found that 19 cases of CAP caused by A. baumannii have been reported in the USA to date [26].…”
Section: Cap Caused By Acinetobacter Baumaniimentioning
confidence: 99%
“…CAP cases caused by A. baumannii are very rare in Europe and USA. A recent USA case report of severe CAP and review of the literature found that 19 cases of CAP caused by A. baumannii have been reported in the USA to date [26].…”
Section: Cap Caused By Acinetobacter Baumaniimentioning
confidence: 99%
“…In Europe and North America, however, A. baumannii is exceedingly rare. A recent USA report found that only 19 cases of severe CAP were caused by this pathogen [24]. Interestingly, in a case-control study in the USA that aimed to characterize the epidemiology of MDR A. baumannii colonization in high-risk nursing home residents, 15% (n = 25) of residents were noted to be colonized, with all isolates being resistant to cephalosporins, monobactam (aztreonam), and quinolones.…”
Section: Accepted Manuscriptmentioning
confidence: 99%
“…Acinetobacter baumannii associated CAP has been reported from countries in tropical or subtropical regions such as Australasia, Asia and Middle East [ 2 , 6 ]. Despite higher incidence in warm climate countries, there have been reported cases in North America as well [ 7 ]. Acinetobacter baumannii is one of the three recognized organisms that can cause severe MDR community acquired pneumonia in addition to Streptococcus pneumoniae and methicillin resistant Staphylococcus aureus [ 8 ].…”
Section: Discussionmentioning
confidence: 99%